Doppler Indices in Prediction of Fetal Outcome in Hypertensive Pregnant Women - Khalid, Mohd; Wahab, Shagufta; Kumar, Vijay; Khalid, Saifullah; Haroon, Soafia; Sabzposh, Noor A (Nepal Journal of Obstetrics and Gynaecology, 2011)
Aim: To determine the role of Color Doppler Sonography in evaluation of fetal outcome in normal and hypertensive pregnant females. Method: The study was carried out on 58 antenatal females (22 normotensive, 36 hypertensive) in their third trimester of pregnancy. After detailed history taking and physical examination, study of various arteries was performed using color Doppler ultrasound TOSHIBA ECCO-CE CX with 3.5 MHz curvilinear probe. Doppler measurements were taken with the mother in recumbent position during fetal inactivity and apnea. Arteries evaluated included – bilateral uterine arteries, umbilical artery, fetal middle cerebral and fetal aorta. Calculation of Systolic/Diastolic ratio(S/D), resistive (RI) and pulsality indices (PI) was done .The indices were correlated with fetal outcome. Results: In our study, 34(94.44%) out of 36 hypertensive patients showed abnormal uterine artery flow of which 11 32.35% had intrauterine growth retardation (IUGR) and 1 Intrauterine death of fetus ( IUD) as fetal outcome. 29 patients of 36 hypertensive patients had abnormal umbilical artery flow of which 1130.5% had IUGR as fetal outcome. Only one patient having severe hypertension had reversed end diastolic velocity (REDV) in umbilical artery and had sudden IUD. Another patient had absent end diastolic velocity (AEDV) and the baby expired 2 days after birth. 28 (77.78%) patients showed brain sparing effect BSE with reduced value of indices in fetal middle cerebral artery. Out of these, 11(30.5%) patients had small for gestational age (SGA) babies and 1(2.7%) had IUD. In hypertensive pregnancies 22 (61.1%) cases showed values of S/D, RI and PI above 2 SD, of which 11(50%) patients had SGA babies. Conclusion: Color Doppler can detect changes in fetomaternal and uteroplacental circulation accurately which seem to correlate strongly with the pregnancy outcome; abnormal indices showing strong correlation with adverse fetal outcome. It helps us to monitor fetal well being, take timely action, plan the treatment and prevent adverse fetal outcome in high risk pregnancies. Keywords: Color Doppler, hypertensive, normotensive DOI: http://dx.doi.org/10.3126/njog.v6i1.5249 NJOG 2011; 6(1): 28-34